Calcified shadow of hilus pulmonis followed with finger‐in‐glove sign of lingular bronchus on the left side. (15th December 2014) - Wang, Mengmei; Liu, Meng; Hu, Ke
Abstract: Tracheobronchial aspiration of foreign body (FB) in adults is not as common as in children. The clinical manifestations are highly variable under different circumstances, considering the state of the patient, the influence of the FB and incipient medical intervention, etc. The lodgement of FB in adults, as in almost all the reports around the world, is dominantly in the right bronchial tree, especially the intermediate and the basal bronchus, because of anatomical reasons. In this case, we reported, a 75‐year‐old woman with a dental piece in her lingular bronchus, not the right side as usual, for at least 10 years had no symptoms or any notice of the aspiration. Surgery and biopsy helped to make definite diagnosis and eventually removal.